Training quality—an unexplored domain in sport science - Haugen, T.; Tonnessen, E.; Bucher Sandbakk, S.; Sandbakk, Ø. (International Journal of Sports Physiology and Performance, 2023)
Performance in sport is influenced by multiple factors wherein natural selection and sport-specific training adaptations are considered particularly important. While selection is closely related to genetics and remains practically unaffected, the utilization of the genetic potential leading to specific adaptation is a mere product of the various stimuli provided through the training process. The training process consists of multiple stages aiming to close the gap between current and desired performance level. These stages in sequence include goal setting, knowledge of the sport-specific requirements, athlete capacity and gap analyses, application of training principles, organization of training load factors (eg, exercises, locomotion modalities, volume, intensity, frequency), and implementation of recovery strategies (eg, rest, nutrition).